A label-free multi-functionalized electrochemical aptasensor based on a Fe3O4@3D-rGO@plasma-polymerized (4-vinyl pyridine) nanocomposite for the sensitive detection of proteins in whole blood. (10th September 2016) - Fang, Shaoming; Dong, Xiaodong; Liu, Shunli; Penng, Donglai; He, Linghao; Wang, Minghua; Fu, Guodong; Feng, Xiaozhong; Zhang, Zhihong
Graphical abstract: Abstract: In this paper, we report a novel label-free electrochemical aptasensor for detecting proteins in whole blood based on a three-component nanocomposite, in which ferriferrous oxide and three-dimensional graphene nanocomposite were modified with the plasma-polymerized 4-vinyl pyridine (Fe3 O4 @3D-rGO@PP4VP). In this novel sensing strategy, large amounts of amino groups in PP4VP facilitated the immobilization of aptamer strands via the strong electrostatic interaction between positively charged ammonium groups of the nanocomposites and negatively charged phosphate groups of aptamers. In the presence of thrombin, LYS (LYS), and platelet-derived growth factor-BB (PDGF-BB), the adsorbed aptamer strands on the developed nanocomposite surface caught the targeted proteins at the electrode interface. The aptamer preferred to be a barrier for electrons and inhibited electron transfer, leading to the decreased peak current of cyclic voltammetry measurements and the increased electron transfer resistance of electrochemical impedance spectroscopy. The determination of the thrombin, PDGF-BB, and LYS concentrations with this novel strategy showed low detection limits of 4.5, 29.4, and 14 pg·mL −1, and the analytical ranges extend from 0.01 to 50, 0.1 to 100, and 0.1 to 200 ng·mL −1, respectively. The resultant aptasensor exhibited high selectivity, acceptable reproducibility, and stability toward thrombin. The aptasensor could be used to detect thrombin in whole blood samples, thereby suggesting its possible application in clinical settings.